Understanding consumer herding behavior in online purchases and its implications for online retailers and marketers - Ali, Dr. Mazhar; Amir, Dr. Huma (Electronic commerce research and applications, 2024)
•This study presented a consumer herding model using the theory of social impact, cue utilization, and information adoption model.•This study measured the direct impact of consumer ratings and sales volume on herding behavior and examined the role of moderators and mediators.•There were negative moderating effects of perceived price and product knowledge and a positive moderating effect of perceived uncertainty.•There were significant mediating effects of perceived information usefulness and perceived quality.•Online retailers and marketers can benefit from using recommended strategies to induce herding behavior in online buying. Herding behavior refers to the imitation of the behavior of the masses. The primary purpose of this study is to determine how herding affects digital purchases. It is an under-researched area in the marketing and consumer behavior context. First, one needs to understand the circumstances under which one is likely to herd. Second, it is yet to be understood how the effect of observing others' buying behavior transmits into herding. Third, there needs to be a better understanding of the role of price in one's tendency to herd. An online experiment with 541 participants was conducted using a 3 (consumer ratings/sales volume/control) × 2 (high involvement product/low involvement product) between-subjects design. LED TV was selected as a high-involvement product and ball pen pack was selected as a low-involvement product. This research study combined three theories to propose a holistic herding model. It used the social impact theory to capture its persuasive impact, the information adoption model to analyze the acceptance of herding information, and the cue utilization theory to assess the inference from herding information in consumer decision-making. Results indicated significant negative moderating effects of perceived price and product knowledge and the positive moderating effect of perceived uncertainty between the relationship of herding cues (star rating and the number of products sold) and herding behavior. In addition, the mediating results of perceived information usefulness and perceived quality were also significant. This herding model provides a holistic view of the herding process beyond limiting it to an attempt to follow others blindly. Therefore, this study has both theoretical as well as managerial implications.